Pengaruh Motivasi Siswa dan Sosial Ekonomi Orang Tua Terhadap Prestasi Belajar Siswa SDN 001 Bulang Kota Batam - A Razak; Muhammad Amin Fauzi; Agnes Puspitasari Sudarmo (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this study is to analyze the influence of student motivation on student achievement, the socio-economic influence of students' parents on student achievement, and the influence of motivation and socioeconomic of parents on student achievement of SDN 001 Bulang Batam City simultaneously. This research was conducted on 66 students. This quantitative study used a survey method with path analysis techniques. Sampling based on the Roscoe technique, using a Likert scale questionnaire that has been compiled and analyzed by six instrument validators and tested for validity and reliability. From the results of the calculation of the influence of student motivation on student achievement with a significance of 0.000 <0.05, the direct effect of motivation on student achievement is 0.5%, the undirect effect is 2.1% while the overall effect is 2.6%. This means that the motivation variable has a significant effect on student achievement. The socio-economic influence of parents on student achievement with a significance of 0.000 <0.05, the direct effect of socio-economy on student achievement is 31.1% and the undirect effect is 2.1% while the overall effect is 33.3%, this means that Parents' socio-economic variables significantly influence student achievement. The effect of motivation and socio-economy together on student achievement with a significance of 0.000 <0.05, the direct effect of student motivation and socio-economic of parents of students together on student achievement is 31.6% and the undirect effect is 4.2% while the overall effect was 35.9%. From the results of the simultaneous calculation of the hypothesis test (Ftest), the value of Fcount = 13.766 and it is known that the value of Ftable = 3.09. Then the value of Fcount = 13.766> Ftable = 3.09. This shows that there is a significant effect with a significance level of 0.000 <0.05. Therefore Ho is rejected and H3 is accepted. This means that there is a significant influence between the variables of student motivation and the socio-economic of students' parents variable simultaneously on the learning achievement of elementary school students in District of Bulang , Batam City.